Ultraweak photon emission induced by visible light and ultraviolet A radiation via photoactivated skin chromophores: in vivo charge coupled device imaging - Prasad, Ankush; Pospíšil, Pavel (Journal of biomedical optics, 2012)
Solar radiation that reaches Earth's surface can have severe negative consequences for organisms. Both visible light and ultraviolet A (UVA) radiation are known to initiate the formation of reactive oxygen species (ROS) in human skin by photosensitization reactions (types I and II). In the present study, we investigated the role of visible light and UVA radiation in the generation of ROS on the dorsal and the palmar side of a hand. The ROS are known to oxidize biomolecules such as lipids, proteins, and nucleic acids to form electronically excited species, finally leading to ultraweak photon emission. We have employed a highly sensitive charge coupled device camera and a low-noise photomultiplier tube for detection of two-dimensional and one-dimensional ultraweak photon emission, respectively. Our experimental results show that oxidative stress is generated by the exposure of human skin to visible light and UVA radiation. The oxidative stress generated by UVA radiation is claimed to be significantly higher than that by visible light. Two-dimensional photon imaging can serve as a potential tool for monitoring the oxidative stress in the human skin induced by various stress factors irrespective of its physical or chemical nature.
Keywords: Equipment Design; analýza selhání vybavení; Radiometry; lidé; Dose-Response Relationship, Radiation; Ultraviolet Rays; fotony; Photons; Reactive Oxygen Species; kůže; Equipment Failure Analysis; radiometrie; Light; Skin; reaktivní formy kyslíku; Radiation Dosage; světlo; design vybavení; dávka záření; vztah dávky záření a odpovědi; ultrafialové záření; Humans